Etika Pembelajaran Sejati Mahasiswa Jurusan Gizi FKM UIN Sumatera Utara - Dwi Ayuning Tyas; Irwansyah Alfaqih; Nadiya Saharani (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this study is to find out the true learning ethics in students majoring in Nutrition FKM UIN North Sumatra. The foundation of a student's character is their ethics. A excellent student needs to be morally upright as well. But not every student is aware of ethics. There are a lot of problems or instances of unethical pupils in the classroom these days. A common issue with student ethics is a lack of respect for professors. For instance, when the instructor is speaking or going over the content, the pupils are not paying attention. For example, lecturers criticize students who like talking loudly enough to communicate with other students while playing games on their phones, as this interferes with class activities and shows disrespect for the speaker. Therefore, it may be said that while some students still act unethically in a classroom setting, others should be aware of and mindful of ethical behavior in such a setting. The aim of this study is to investigate how students apply and understand student ethics in a classroom setting. Both observation and interviewing are used in this study. Thirty sources and five indicators were employed in this study, which included DIII nursing students studying health information management.